Catalysis: Low‐Temperature Remediation of NO Catalyzed by Interleaved CuO Nanoplates (Adv. Mater. 26/2014). (July 2014) - Auxilia, Francis Malar; Ishihara, Shinsuke; Mandal, Saikat; Tanabe, Toyokazu; Saravanan, Govindachetty; Ramesh, Gubbala V.; Umezawa, Naoto; Hara, Toru; Xu, Ya; Hishita, Shunichi; Yamauchi, Yusuke; Dakshanamoorthy, Arivuoli; et al.
<x xml:space="preserve">Abstract</x> On page 4481, H. Abe, K. Ariga, S. Ishihara, and co‐workers demonstrate that single‐crystalline 001 nanoplates of an abundantly available copper oxide, when interleaved with each other in the form of a flower‐like microstructure, remediate toxic nitrogen oxides into environmentally benign nitrogen more efficiently at low temperatures than preciousmetal catalysts such as platinum, palladium, and even rival rhodium. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>